Therapeutic Potential of Calcium Channel Blockers in Neuropsychiatric, Endocrine and Pain Disorders - Aarish Manzar; Aleksandar Sic; Crystal Banh; Nebojsa Nick Knezevic (Cells)
Calcium channel blockers (CCBs), originally developed for cardiovascular indications, have gained attention for their therapeutic potential in neuropsychiatric, endocrine, and pain-related disorders. In neuropsychiatry, nimodipine and isradipine, both L-type CCBs, show mood-stabilizing and neuroprotective effects, with possible benefits in depression, bipolar disorder, and schizophrenia. In endocrinology, verapamil, a non-dihydropyridine L-type blocker, has been associated with the preservation of pancreatic β-cell function and reduced insulin dependence in diabetes. CCBs may also aid in managing primary aldosteronism and pheochromocytoma, particularly in patients with calcium signaling mutations. In pain medicine, α2δ ligands and selective blockers of N-type and T-type channels demonstrate efficacy in neuropathic and inflammatory pain. However, their broader use is limited by challenges in central nervous system (CNS) penetration, off-target effects, and heterogeneous trial outcomes. Future research should focus on pharmacogenetic stratification, novel delivery platforms, and combination strategies to optimize repurposing of CCBs across disciplines.